“Is dopamine involved in Alzheimer's disease?” - Martorana, Alessandro; Koch, Giacomo (Frontiers in Aging Neuroscience, 2014)
Alzheimer’s Disease (AD) is a neurodegenerative disorder characterized by progressive cognitive decline and dementia. Recent advances indicate that AD pathogenesis appears more complex than its mere neuropathology. Changes in synaptic plasticity, neuronal disarray and cell death are pathways commonly recognized as pathogenic mechanisms of AD. It is thought that the altered metabolism of certain membrane proteins may lead to the production of amyloid (Aβ) oligomers that are characterized by an highly toxic effect on neurotransmission pathways, such as those mediated by Acetylcholine. The interaction of Aβ oligomers with these neurotansmitters systems would in turn induce cell dysfunction, neurotransmitters signaling imbalance and finally lead to the appearance of neurological signs. In this perspective, it is still debated how and if these mechanisms may also engage the dopaminergic system in AD. Recent experimental work revealed that the dopaminergic system may well be involved in the occurrence of cognitive decline, often being predictive of rapidly progressive forms of AD. However a clear idea on the role of the dopamine system in AD is still missing. Here we review the more recent evidences supporting the notion that the dopaminergic dysfunction has a pathogenic role in cognitive decline symptoms of AD.